Педагогические инновации в формировании навыков академической речи (Journal of Educational Sciences, 2022)
Academic speech skills are rapidly developing following the requirements of modern society. Essential is expressing yourself in English using academic words and terms. Therefore, various innovative technologies are used to inform academic speech skills in teaching English. One of them is teaching English through podcasts. In this article, we have used English podcasts to complement the curriculum as the most effective way to develop academic English speaking skills. The study involved 2 groups of 2nd year students specializing in foreign languages. One group was experimental, and the other was control. Group A, chosen as the experimental group, used podcasts in English to teach English. The learning process in group B, i.e., the control group, was limited to the curriculum. An interview was conducted at the end of the study. As a result of the study, Group A students who used podcasts to teach English developed academic speaking skills; that is, they made academic-level sentences using more academic words and terms. On the other hand, group B students had a good level of English but a low level of academic English. When speaking English, they used everyday English words more often than terms of an academic degree.The method chosen in the study, aimed at developing the skills of academic speech in English, showed a positive result. Students' academic speech skills were developed by watching podcasts in English.Key words:academic speaking skills, podcasts, English , innovation, interviews